Prevalence of Risk Factors for Liver Disease in a Random Population Sample in Southern Germany - Huetter, M.-L.; Fuchs, M.; Hänle, M. M.; Mason, R. A.; Akinli, A. S.; Imhof, A.; Kratzer, W.; Lorenz, R. (Zeitschrift für Gastroenterologie, 2014)
Background: Chronic liver disease leads to fibrosis and cirrhosis of the liver. This may, in turn, result in chronic liver failure or the development of hepatocellular carcinoma (HCC). Main risk factors for chronic liver disease are viral hepatitis and alcoholism. The present study assessed a randomly selected population in southern Germany for risk factors for chronic liver disease such as fatty liver disease, viral hepatis infection and life-style factors. In addition, the potential association with elevated liver enzymes was investigated.Methods: A total of 2256 subjects (1182 females, 1074 males), aged 18 − 65 years, participated in the study. Each subject underwent a standardized ultrasound examination, and anthropometric and biochemical assessments. Test subjects were randomly selected from the general population of a town in southwestern Germany. Data were acquired from November to December 2002 without further follow-up.Results: Several factors were found to be associated with chronic liver disease in the study population. Alcohol consumption > 20 g/d was seen in 18.1 % (n = 409). Metabolic syndrome was diagnosed in 5.9 % (n = 132). The number of people with a BMI greater than 25 kg/m² was 45.1 % (n = 1017). The prevalence of subjects with chronic hepatitis B was 0.7 % (n = 15), that of anti-HCV positive patients, 0.6 % (n = 15). Elevated gGT was seen in 10.4 % (n = 14) of the patients. Prevalence of hepatic steatosis was 25.0 % (n = 564).Conclusions: Many cases of chronic liver disease could be prevented by healthy nutrition, optimized medical treatment of associated disorders, and prevention strategies such as routine vaccination, in particular, against hepatitis B virus (HBV).
Keywords: Querschnittsstudien; Ultraschall; Fettleber; Hepatitis B; Hepatitis C